Analisis Pemanfaatan Aplikasi TikTok dalam Meningkatkan Penjualan UMKM Sektor Kuliner di Kota Makassar - Nur Afiah; Muhammad Hasan; Ratnah S; Nur Arisah (Ideas Publishing, 2022)
Marketing is the most important part of a business. Marketing does not only look at the side of unique products, cheap and attractive prices, and product availability for consumers. During the current Covid-19 pandemic, where the digital era is increasingly advanced, it is necessary to carry out marketing activities, one of which is by utilizing social media such as TikTok. This study aims to determine the use of the TikTok application in increasing sales of the culinary sector SMEs in the city of Makassar. In this research, the method used is descriptive qualitative approach. This research is a field research. The data used from this research are primary and secondary data, with data collection techniques of observation, interviews and literature study. The result of this research is Media Promotion through TikTok is an effective promotional tool to increase sales.